The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/s1368980019003173
|View full text |Cite
|
Sign up to set email alerts
|

Estimating and differentiating maternal feeding practices in a country ranked first in childhood obesity

Abstract: Objective:Mexico ranks first in childhood obesity worldwide. However, little is known about the factors influencing maternal feeding practices. The present study aimed to estimate the prevalence of feeding practices and explore associations between weight concern, weight perception, sociodemographic characteristics and those feeding practices.Design:Cross-sectional.Setting:North-eastern Mexico.Participants:Mothers aged ≥18 years who were in charge of feeding a singleton child aged 2–6 years with no endocrine d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies are shown in Table 1 . The studies were published between 2001 and 2022, conducted in the US ( n = 12) [ 21 , 24 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ], Australia ( n = 6) [ 26 , 27 , 75 , 76 , 77 , 78 ], Brazil ( n = 4) [ 28 , 30 , 50 , 79 ], Sweden ( n = 4) [ 22 , 80 , 81 , 82 ], China ( n = 2) [ 83 , 84 ], the Netherlands ( n = 1) [ 85 ], Ethiopia ( n = 1) [ 29 ], the UK ( n = 1) [ 86 ], Mexico ( n = 1) [ 87 ], South Korea ( n = 1) [ 88 ], Portugal ( n = 1) [ 23 ], India ( n = 1) [ 25 ], and France ( n = 1) [ 74 ]. The study designs were a cross-sectional study ( n = 32) and a cohort study ( n = 3) [ 23 , 26 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“… Effects of concern about child overweight on restrictive feeding (evaluated using OR) [ 30 , 71 , 79 , 87 , 88 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The strengths of this study are the well-defined population and robust statistical analysis. We consider this study is particularly relevant, since CKD prevalence and mortality rate have doubled in Mexico over the last 20 years (Dávila-Torres, González-Izquierdo & Barrera-Cruz, 2015;Salinas Martínez et al, 2020). For this reason, larger-scale studies are required in the Mexican population in order to determine the predictive values of urinary MMP-9/UCr, including sensitivity, positive predictive value, negative predictive value, probability ratio for positive test, probability ratio for negative test and area under the ROC curve.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' feeding practices have shown to be associated with various types of parental perceptions of children's weight status. Parents who perceived their children as overweight/obese are more likely to monitor and restrict children's food intake [17][18][19], while parents who perceived their children as underweight are more likely to pressure their children to eat more [17,20]. Parental concern and dissatisfaction regarding children's weight status have also found to be associated with the feeding practices of restriction and pressure to eat [21,22].…”
Section: Introductionmentioning
confidence: 92%